Artificial Intelligence and Neuroimplant Applications in Neurological Rehabilitation Following Spinal Cord Injury Surgery: A Systematic Review - Muhammad Fadil; Rady Dwipayana (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
In recent years, there has been a significant surge in discussions surrounding artificial intelligence (AI), accompanied by a corresponding increase in its practical applications across various aspects of daily life, including the medical industry. Notably, even in the highly specialized field of spine surgery, AI has been utilized for differential diagnosis, preoperative evaluation, and enhancing surgical precision. Many of these applications have begun to reduce the risk of intraoperative and postoperative complications, as well as improve postoperative care. This article aims to present an overview of studies on the use of AI in neuroregeneration and neurological rehabilitation following spinal cord injury (SCI) surgery. The methodology involves identifying highly cited papers through ScienceDirect and Google Scholar, conducting a comprehensive review of various types of studies, and summarizing neurological rehabilitation applications after SCI surgery to enhance clinicians’ understanding for future utilization. Recent studies indicate that AI technologies are employed in several areas of spine surgery and neurosurgery, including traumatic brain injury and SCI. SCI presents complex physiological, psychological, and cognitive challenges. Assessment of residual neural function and post-injury functional status is conducted to evaluate the extent of recovery, though concerns remain regarding the validity and generalizability of these assessment outcomes.